Tinjauan Hukum Islam Terhadap Pembayaran Jujuran Dalam Pernikahan Adat Banjar di Kelurahan Senyerang Jambi - Siti Hajrah; Kadenun Kadenun; Diyan Putri Ayu (Social Science Academic, 2023)
real goal of marriage is to build a prosperous family, not just a connection between two genders. One of the pillars in marriage is the dowry. Dowry is a husband's gift to the wife. Uniquely in Indonesia, dowry in certain customs, the amount is determined. one of them is banjar custom in Senyerang Village. In determining the dowry they have a tradition known to be honest. In this study, it is categorized as field research, and is ethnographic research. This research not only describes certain characteristics, but also analyzes why and how these things happen. The data collection techniques used in this study were in-depth interviews, observations and literature studies. The results showed that the dowry and honesty in the Banjar community in Senyerang Village were different, the amount or amount of honesty was influenced by several factors, Among them: the level of education, the parents of women and the level of beauty. But everything remains within the agreement of both parties. The review of Islamic law analyzes the honest law that exists in the society, which is contained in the honesty, namely help and the law is okay as long as it does not bring mudharatan according to Islamic teachings.